OCCUPATIONAL HAZARDS IDENTIFICATION AND THEIR RISK ASSESSMENT DURING THE CONSTRUCTION OF HEAD RACE TUNNEL IN MIDDLE BHOTEKOSHI HYDROELECTRIC PROJECT - Lama, Chheku; Sah, Dinesh Prasad; Kumar Mishra, Anjay (International Journal of Research -GRANTHAALAYAH, 2019)
Construction of hydro power tunnel generates lots of occupational hazards. Due to different types of occupational hazards prevailed in tunnel construction, occupational accidents and diseases may affect health and safety of the workers. The main objective of this research was to identify the occupational hazards and assess their risks level. Head Race Tunnel of Middle Bhotekoshi Hydroelectric Project-102MW (MBKHEP) was selected for the study. This study has been carried out by utilizing the data collected from the duly filled semi structured questionnaires by the Employers’, Consultants’ and Contractors’ personnel. Moreover and key informant interview. Risk level of rock fall hazard has been revealed as the highest with risk score of 21.5 and fall under “Critical” risk level rating. Electric hazard and vibration have been found to have the risk score of 16 and 13.35 respectively both having “High” level of risk rating. Toxic gases like ammonia gases etc., dust hazards, hot and humid work environment, heat and humidity, tripping, ergonomics, chemical spills, oxygen deficiency, lighting, noise/sound and unprotected edges have been found to have risk scores 10,10, 9.5,9.215,9,8.65,8.1,8.1,7.6,6.75,6 respectively which all fall under the risk level rating of “Moderate”. Other hazards having “Low” risk rating level were alcoholism, fall from platform, job dissatisfaction, job Insecurity, hit by aggregate, radiations, mechanical struck, slippery, snake bites, water inundation, deadline pressure and bat biting with respective risk scores 5.25,4.8,4.6,4.45,4.3,4,4,4,4,3,2.85,2.